A SIMULATION ANALYSIS OF WIDE BANDGAP SEMICONDUCTOR - BASED POWER FACTOR CORRECTOR (PFC) - BURKOVSKIY, YAROSLAV; ZINKOVSKIY, YURIY (Herald of Khmelnytskyi National University. Technical sciences, 2023)
This paper details the progressive findings from comprehensive research and computer-based simulations centered on enhancing grid power factor correctors (PFCs). The study particularly focuses on the integration of semiconductors constructed from a wide band-gap materials, namely silicon carbide (SiC) and gallium nitride (GaN). The utilization of these sophisticated materials is a game-changer in the performance of modern power converters. They play a significant role in substantially reducing the static and dynamic energy losses.Additionally, these improvements lead to an increase in the frequency at which the corrector operates. This enhancement is not just about efficiency; it also contributes to the practical aspects of the device. There is a noteworthy reduction in the PFC's size and weight, making the units more compact and manageable. One of the standout benefits is the decreased heat generation, which is crucial in maintaining the longevity and reliability of the device.A comprehensive review and analysis of modern studies focusing on power factor correction technology were undertaken, forming the foundation for the research. Subsequently, a novel simulation methodology for PFCs was introduced, executed within the LTSpice XVII schematic SPICE simulator environment. The simulation yielded data visualized through current and voltage graphs and component temperatures, highlighting main power losses within the PFC's components. Furthermore, the research produced the input current spectrum of the corrector, verifying its adherence to the stringent IEEE 519-2022 global standard.One of the key outcomes of these computer-based simulations was the creation of a physical prototype. This real-world model serves as a bridge between theoretical strategies and practical solutions, providing a basis for additional experimentation.
Keywords: Power Factor Corrector (PFC); Gallium Nitride (GaN); Silicon Carbide (SiC); SPICE simulation; LTSpice XVII; Wide Band-gap Semiconductors